Reversal of multidrug resistance in human lung cancer cells by delivery of 3-octadecylcarbamoylacrylic acid–cisplatin-based liposomes - Song J; Ren W; Xu T; Zhang Y; Guo H; Zhu S; Yang L (Dove Medical Press, 2017)
Juan Song, Weifang Ren, Tingting Xu, Yi Zhang, Hongyu Guo, Shanshan Zhu, Li Yang Department of Pharmaceutics, College of Pharmacy, Shenyang Pharmaceutical University, Shenyang, Liaoning, People’s Republic of China Abstract: Liposome-based drug delivery system would be an innovative and promising candidate to circumvent multidrug resistance (MDR) of cisplatin (CDDP). However, the reversal efficacy of liposomal CDDP was severely impaired by weak cellular uptake and insufficient intracellular drug release. In this study, 3-octadecylcarbamoylacrylic acid–CDDP nanocomplex (OMI–CDDP–N)-based liposomes (OCP-L) with high cellular uptake and sufficient intracellular drug release were designed to circumvent MDR of lung cancer. OMI–CDDP–N was synthesized through a pH-sensitive monocarboxylato and an O→Pt coordinate bond, which is more efficient than CDDP. Also, OCP-L incorporated with OMI–CDDP–N could induce effective cellular uptake, enhanced nuclear distribution, and optimal cellular uptake kinetics. In particular, OCP-L presented superior effects on enhancing cell apoptosis and in vitro cytotoxicity in CDDP-resistant human lung cancer (A549/CDDP) cells. The mechanisms of MDR reversal in A549/CDDP cells by OCP-L could attribute to organic cation transporter 2 restoration, ATPase copper-transporting beta polypeptide suppression, hypoxia-inducible factor 1 α-subunit depletion, and phosphatidylinositol 3-kinase/Akt pathway inhibition. These results demonstrated that OCP-L may provide an effective delivery of CDDP to resistant cells to circumvent MDR and enhance the therapeutic index of the chemotherapy. Keywords: 3-octadecylcarbamoylacrylic acid-cisplatin nanocomplexes, liposomes, cellular uptake, multidrug resistance, therapeutic index